2021
DOI: 10.1093/jn/nxaa399
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Intrahousehold Bargaining Power is Associated with Child Nutritional Status in Nepal

Abstract: Background Women's intrahousehold bargaining power is an important determinant of child nutrition in Nepal, but a better understanding is needed on how men's bargaining power is related to child nutrition. Objectives We examined the relation of women's and men's household bargaining power with child height-for-age z score (HAZ). Methods We analyzed cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Thus, we do have some evidence that some factors that positively change status do affect eating patterns, potentially through a pathway of increased bargaining power, agency and decision-making power. Recent studies in Nepal have found that women's bargaining power was associated with child nutritional status, and extend the literature on seeing how this affects women's own nutrition (Kulkarni et al, 2021). However, we find that living in food insecurity holds women back from this advantage.…”
Section: This Contrasts With Our Hypothesis and Other Recent Research Insupporting
confidence: 76%
“…Thus, we do have some evidence that some factors that positively change status do affect eating patterns, potentially through a pathway of increased bargaining power, agency and decision-making power. Recent studies in Nepal have found that women's bargaining power was associated with child nutritional status, and extend the literature on seeing how this affects women's own nutrition (Kulkarni et al, 2021). However, we find that living in food insecurity holds women back from this advantage.…”
Section: This Contrasts With Our Hypothesis and Other Recent Research Insupporting
confidence: 76%
“…Some studies have shown that men have limited participation in direct decision‐making related to breastfeeding and complementary feeding, suggesting that gendered constructed norms obstruct men's involvement in child nutrition (Dewey & Begum, 2011 ; Kansiime et al, 2017 ). Studies from Nepal found that males are more inclined to get involved in child nutrition in cases when they participate in social networks (Kulkarni et al, 2021 ) or when children are sick (Cunningham et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies (Kulkarni et al, 2020;Nankumbi & Muliira, 2015) have shown that traditional gender roles can impact negatively child health through unequal family decision-making and reduced paternal support. Another important aspect to consider is that fathers are not usually included in studies on feeding practices (Harris et al, 2018).…”
Section: Discussionmentioning
confidence: 99%